The interplay of co-occurring ecosystem engineers shapes the structure of benthic communities – a mesocosm experiment - Gusmao, Joao Bosco; Rühmkorff, Sarah; Kraufvelin, Lucinda; Meysick, Lukas; Pansch, Christian (Frontiers in Marine Science, 2024)
Introduction Ecosystem engineers play a pivotal role in shaping habitats through their activities and presence. In shallow Baltic waters, seagrasses, patch-forming mussels, and infaunal clams modify soft bottom habitats, impacting benthic community structure. While the individual effects of these ecosystem engineers are well studied, interactions among co-occurring engineers are poorly understood. Methods We conducted a mesocosm experiment to assess the independent and combined impacts of seagrass (Zostera marina), epifaunal mussels (Mytilus spp.), and infaunal clams (Macoma balthica) on invertebrate colonization in soft sediments. Results Our findings reveal significant engineer-driven alterations in macrofaunal community structure. Combined engineer effects diverged from individual impacts, indicating potential synergies or antagonisms in sediment (re)colonization. Notably, a higher number of engineer species positively affected the diversity of settled macrofauna, with the lowest macrofaunal abundance and biomass but the highest Shannon diversity found in the presence of all three engineers. Discussion Results suggest that seagrass, mussels, and clams influence benthos through larval settlement and sediment biogeochemistry, providing insights into the distinct roles of habitat-forming organisms in shaping the benthic communities in coastal ecosystems of the Baltic Sea.